A new xanthone dimer and cytotoxicity from the stem bark of calophyllum canum - Bakhtiar, M. Taher; Wan Salleh, Wan Mohd Nuzul Hakimi; Alkhamaiseh, Suhaib Ibrahim; Ahmad, Farediah; Rezali, Mohd Fazlin; Darnis, Deny Susanti; Hasan, Choudhury Mahmood (De Gruyter, 2020)
A phytochemical investigation of the stem bark of Calophyllum canum resulted in the isolation of a new xanthone dimer identified as biscaloxanthone (1), together with four compounds; trapezifoliaxanthone (2), trapezifolixanthone A (3), taraxerone (4) and taraxerol (5). The structures of these compounds were determined via spectroscopic methods of IR, UV, MS and NMR (1D and 2D). The cytotoxicity of compounds 1–3 were screened against A549, MCF-7, C33A and 3T3L1 cell lines, wherein weak cytotoxic activities were observed (IC50 > 50 μM).